The Pursuit of Metals and the Ideology of Improvement in Early Modern Sápmi, Sweden. - Naum, Magdalena (Journal of Social History)
The article examines the ideology of improvement in the context of seventeenth- and eighteenth-century mining in northern Sweden in the province of Sápmi. It discusses how the rhetoric of improvement and "civilizing" projects were intertwined with the mining enterprises; how they informed the regulatory and disciplinary ordinances issued for the region; and how the ideas of reform, discipline, and civility were materialized in the physical organization of the metal works. Contextualizing these issues within state policies aiming to better incorporate Sápmi into the mainstream economy and culture of Sweden, the article suggests that mines and processing works were singled out as suitable places for such transformation due to their spatial and organizational characteristics. The study is informed by contemporary political thinking as well as by Foucauldian perspectives on governmentality and its spatial dimensions.